2020
DOI: 10.31234/osf.io/5wxtf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“Be a Man”: The Role of Social Pressure in Eliciting Men’s Aggressive Cognition

Abstract: [Pre-print accepted for publication in Personality and Social Psychology Bulletin on November 20, 2020.] Threatening a man’s manhood—but not a woman’s womanhood—elicits aggression. In two studies, we found evidence that this aggression is related to the social pressure men experience to “be a man.” In Study 1a, we conducted an exploratory factor analysis to isolate participants’ (N = 195; Mage = 19.92) differential motivations for conforming to gender norms. Study 1b then showed that pressure to be masculine m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…We do not know if it is the act of physical punishment or a woman demonstrating power over a young boy that leads to the varied responses from our sample of men. These results may be consistent with Stanaland and Gaither's (2021) findings especially for young men when they feel that their masculinity is threatened. Aggressive language appears to be a reaction to experiencing shameinduced negative emotions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We do not know if it is the act of physical punishment or a woman demonstrating power over a young boy that leads to the varied responses from our sample of men. These results may be consistent with Stanaland and Gaither's (2021) findings especially for young men when they feel that their masculinity is threatened. Aggressive language appears to be a reaction to experiencing shameinduced negative emotions.…”
Section: Discussionsupporting
confidence: 89%
“…The resulting internalized shame is a debilitating experience, leaving a man to believe he is defective and unworthy of kindness (Reilly et al, 2014), and has been found to correlate with externalizing behaviors, such as aggression toward women (Dutton & Golant, 1995). Stanaland and Gaither (2021) determined that men, especially younger men, respond predominantly with aggression when they perceive that their masculinity is threatened. Their research indicated that this was par ticularly true for men who value the opinions of others and attempt to adhere to strict traditional gender norms.…”
Section: Psi Chi Journal Of Psychological Researchmentioning
confidence: 99%
“…Similar to recent research that has revealed parallel patterns between undergraduate students and representative adult samples when examining HM’s relationship to political attitudes—including evaluations of Trump and Biden (Vescio and Schermerhorn, 2021), the present work also finds relatively consistent patterns when examining responses to COVID-19. Additionally, while beliefs about masculinity are relatively consistent between samples of undergraduate and adult men, masculinity is more fragile for younger (vs. older) men (Stanaland and Gaither, 2021). The current research does find that among our student (but not non-student) sample, HM was associated with disapproval of federal mandates.…”
Section: Discussionmentioning
confidence: 98%
“…We aim to contribute novel insight to this discussion by documenting how stereotype content and culture intersect to influence the extent to which positive stereotyped trait expectations constrain the self. Although men and women both face pressures to act in gender-normative ways—and men may experience gendered pressures negatively (Stanaland & Gaither, 2020)—our research shows that when we directly compare women’s and men’s experience of positive-gendered trait expectations, we observe that women experience such expectations more negatively than men, in part due to women facing pressures to act in interdependent ways, which conflict with the Western prioritization of independence and autonomy. Thus, our research offers a new perspective on how gender stereotypes place an undue burden on women relative to men, even when the gendered traits expected of women are framed as desirable and valued qualities.…”
Section: Discussionmentioning
confidence: 78%